2018
DOI: 10.11606/s1518-8787.2018052000406
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre raça/cor da pele e parto prematuro: revisão sistemática com meta-análise

Abstract: OBJECTIVE To analyze the association between race/skin color and the occurrence of prematurity.METHODS Meta-analysis with observational studies, selected by a systematic review in the bibliographic databases Medline and Biblioteca Virtual da Saúde with the descriptors: “Race or ethnic group” and “ethnicity and health” associated with the words “infant premature” and “obstetric labor premature”. Articles published in the period from 2010 to 2014, of the observational epidemiological type, in Portuguese, English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
0
13
0
4
Order By: Relevance
“…It remains unclear whether the difference in cervical length between populations is due to environmental factors that would interfere in population growth capability, such as nutrition and access to health services, or due to intrinsic characteristics such as ethnicity/race [ 30 ] and anthropometric features. It is clear that there is an important association amid socioeconomic status and race in all western world, nevertheless, few included studies described information of short cervix for race/skin color groups and, in our study, it is difficult to analyze this data and infer association between race and short cervix without possible bias.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether the difference in cervical length between populations is due to environmental factors that would interfere in population growth capability, such as nutrition and access to health services, or due to intrinsic characteristics such as ethnicity/race [ 30 ] and anthropometric features. It is clear that there is an important association amid socioeconomic status and race in all western world, nevertheless, few included studies described information of short cervix for race/skin color groups and, in our study, it is difficult to analyze this data and infer association between race and short cervix without possible bias.…”
Section: Discussionmentioning
confidence: 99%
“…The PTB rate in the RP cohort of the present study, however, did not differ between newborns of white, brown, and black mothers, contradicting other studies. Oliveira et al ( 29 ), in a systematic review with meta-analysis of articles published from 2010 to 2014, observed that black women are 1.5 times more likely to have PTB compared to non-black women. A possible explanation for not detecting the association is that there is really no difference in preterm birth rates between black and brown compared to white mothers in RP.…”
Section: Discussionmentioning
confidence: 99%
“…The factors associated to breastfeeding in the first hour of life include newborn weight, delivery route (5) , gestational age, and complications during birth and the immediate post-partum period. The maintenance of EBF in the first six months and the practice of BF in the first two years of life are intimately related to age (5) , education (6) and maternal skin/ethnicity (7) , marital status (8) and socioeconomic condition (6) , number of prenatal consultations and type of delivery (5) and child-related factors, such as sex (9) , appropriate weight for gestational age (5) , early skin-to-skin contact (5)(6) , vitality at birth (5) , and use of pacifier (9) .…”
Section: Introductionmentioning
confidence: 99%